The Tlokwe City Council Dolomite Management Desk: a communication and relationship management perspective. (2nd January 2016) - Wiggill, Magrita Nicolene
ABSTRACT: Two-way communication and strong relationships between government and affected communities are necessary to enhance the latter's resilience to disaster risks. The Tlokwe City Council (TCC) in the North-West province, South Africa, is facing a dolomite and sinkhole disaster risk that threatens the safety of several residential areas, including informal settlements. A dolomite disaster risk reduction (DRR) management system such as the TCC Dolomite Management Desk (DMD) can be used to facilitate two-way communication and strong relationships between government and the affected communities. Semi-structured interviews with two different groups of people were conducted and the responses evaluated to determine in what way DRR communication via the Tlokwe DMD served to establish strong relationships between the TCC and the affected community. It was found that the two groups of interviewees had contradictory views on the risk communication and quality of relationships as facilitated by the Tlokwe DMD. These views illuminated the predicament of communicating about the dolomite and sinkhole risk. The Tlokwe DMD is unique in South Africa and its ability to enable communication and strong government–community relationships needs to be developed further. Recommendations are made in this regard.